Bamboo shapes the fine-scale richness, abundance, and habitat use of small mammals in a forest fragment - André, Clariana Lima [UNESP]; Côrtes, Marina Corrêa [UNESP]; Heming, Neander Marcel; Galetti, Mauro [UNESP]; Alves, Rafael Souza Cruz [UNESP]; Bovendorp, Ricardo Siqueira [UNESP] (Springer Nature, 2022)
A classic question in community ecology is how species coexist within a community. Studies have sought to understand how species occurrence vary according to habitat structure, space, food, predators, and competitors. Small mammals are widely used as a model system in community ecology, since they represent the most diverse group of mammals in the neotropical forests. Hence, we investigated whether microhabitat features, food resource (fruits), and presence of medium and large mammals can explain fine-spatial scale richness, abundances, and habitat use of small mammals in a forest in Brazil. Three species represented 83% of all captured individuals (Didelphis albiventris, Oligoryzomys nigripes, Akodon montensis). Species richness, abundance, and habitat use of small mammals were affected positively by the distance of bamboo (Chusquea sp.) thickets. The occurrence of predators (carnivores and omnivores) and potential competitors (large herbivores), however, did not affect richness, abundance, and habitat use of small mammals at small spatial scales. Our findings suggest that the bamboo patches can influence spatial distribution and shape small mammal communities in tropical forests.
Keywords: Atlantic rainforest; Brazil; Caetetus Ecological Station; Chusquea; Community ecology; Grid method